GAMBARAN BENTUK DAN PENYEBAB KECEMASAN DEWASA AWAL PADA MASA TRANSISI PANDEMI MENUJU ENDEMI DI JAKARTA - Sitti Rahmah Marsidi; Ismiati Ismiati; Maulani Baqiah; Natalia Natalia; Ratieh Michelia Pattinaya; Selsafania Eksanti; Sri Agustini (Sekolah Tinggi Pariwisata Mataram, 2022)
The change from a pandemic to an endemic causes individuals to adapt. When adjusting, not all individuals can successfully live it calmly. One of the conditions that can be felt by individuals related to the transition from a pandemic to endemic is anxiety. This study aims to understand the forms of anxiety and the causes of early adult anxiety during the transition from pandemic to endemic in Jakarta. The approach used is a qualitative approach, with data collection techniques through interviews and observation. There were 3 respondents, with a high anxiety score (BAI). The results showed that the reasons for the respondents' anxiety were due to the fear of Covid-19 transmission again, decreased income, rising prices for necessities and high costs of education, and the need to return to activities in the office that had been carried out at home (WFH). The forms of anxiety that occur can be described in two forms, namely physiological and psychological anxiety